Painting successful watercolours from photographs - Kersey, Geoff (Tunbridge Wells, ENGLAND Search Press, 2015)
Artists who work from photographic source material need to learn how to adapt and improve in order to create a successful painting. Geoff Kersey is a master of this way of working, and here he shows how it is done. Reference photographs, colour charts and preparatory sketches are shown alongside all the finished paintings in this book, with full details of the adaptations and creative processes involved. There are plenty of clear tips and advice, and an illustrated glossary of all the painting terms used. Readers who want much more advice on adapting from reference sources than is provided in step by step painting books will have all they need here, and there are dozens of beautiful paintings to inform and inspire them
Arts (Drawing)
1 13
CHILDFENSC, NEW
Keywords: Akvarellmålning; Painting from photograph; Watercolor painting -- Technique